Nearest star : the surprising science of our sun - Golub, L. (Leon); Pasachoff, Jay M. (Cambridge University Press, 2014)
"How did the Sun evolve, and what will it become? What is the origin of its light and heat? How does solar activity affect the atmospheric conditions that make life on Earth possible? These are the questions at the heart of solar physics, and at the core of this book. The Sun is the only star near enough to study in sufficient detail to provide rigorous tests of our theories and to help us understand the more distant and exotic objects throughout the cosmos. Having observed the Sun using both ground-based and spaceborne instruments, the authors bring their extensive personal experience to this story revealing what we have discovered about phenomena from eclipses to neutrinos, space weather, and global warming. This Second Edition is updated throughout, and features results from the current spacecraft that are aloft, especially NASA's Solar Dynamics Observatory, for which one of the authors designed some the telescopes"--Provided by publisher.